2018
DOI: 10.17951/pjss.2017.50.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Activity of dehydrogenases in clay soil exposed to quaternary ammonium salts with iodine anion

Abstract: , and pH 7.13 in 1 M KCl. QAS were added to soil at the dosages: 0, 10, 100, and 1,000 mg·kg -1 . Activity of dehydrogenases was assayed on days: 1, 14, 35, and 70. The obtained results have shown that the treatment of soil with quaternary ammonium salts along with the iodine anion caused decrease in the activity of dehydrogenases. This inhibition increased with the increase of QAS dosages and increase with alkyl chains in cations. Analysis of variance η 2 indicatedthat the type of QAS had the biggest impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In TEP-MS, peaks at 721–754 cm –1 and peaks at 1200–1300 are related to P-C stretching and P-CH 2 -R deformation bands, respectively . Moreover, the C–H bond at 2926 cm –1 and the ether bond (C–O) at 1072, 1161, and 1234 cm –1 are also noted in TEA-TFMS . It was noticed that the treated Na-Mt shows a minor shift of the Si–O stretching vibration originally recorded at 983 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In TEP-MS, peaks at 721–754 cm –1 and peaks at 1200–1300 are related to P-C stretching and P-CH 2 -R deformation bands, respectively . Moreover, the C–H bond at 2926 cm –1 and the ether bond (C–O) at 1072, 1161, and 1234 cm –1 are also noted in TEA-TFMS . It was noticed that the treated Na-Mt shows a minor shift of the Si–O stretching vibration originally recorded at 983 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also showed the effect of quaternary ammonium salts (QAS) and other ILs on the activity of soil enzymes. These demonstrated, among others, a decrease in the activity of DHA under the influence of QAS with iodine anion [ 61 ] or the activity of o-diphenol oxidase under the influence of QAS with hexafluorophosphate anion [ 62 ]. These effects were observed to increase both with the increase in the dose of ILs and the level of elongation of alkyl substituent in the cation [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activity and stability are the main parameters to determine the applicability of an enzyme. Several research groups have studied the effects of detergents, solvents, salts, and polymers on the catalytic performance of enzymes, including lipases, to expand their applications.…”
Section: Introductionmentioning
confidence: 99%